2011
DOI: 10.1021/ic202029e
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine Analogues of the Antimetastatic Ru(III) Complex NAMI-A Targeting Non-Covalent Interactions with Albumin

Abstract: A series of pyridine-based derivatives of the antimetastatic Ru(III) complex imidazolium [trans-RuCl(4)(1H-imidazole)(DMSO-S)] (NAMI-A) have been synthesized along with their sodium-ion compensated analogues. These compounds have been characterized by X-ray crystallography, electron paramagnetic resonance (EPR), NMR, and electrochemistry, with the goal of probing their noncovalent interactions with human serum albumin (hsA). EPR studies show that the choice of imidazolium ligands and compensating ions does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
76
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 83 publications
9
76
1
Order By: Relevance
“…Initial rapid binding of KP1019 takes place in a non-covalent manner at the hydrophobic binding sites of HSA, however after a longer incubation time the type of the interaction is converted slowly to a protein-coordinated form [33]. Similar behavior of NAMI-A and its pyridine analogues was found recently based on mainly electron paramagnetic resonance spectroscopic measurements [34,35]. A binding ratio of four KP1019 complex anions on a single HSA molecule was determined by CD and confirmed by inductively coupled plasma atomic emission spectroscopic (ICP-AES) method [23].…”
Section: Introductionsupporting
confidence: 72%
“…Initial rapid binding of KP1019 takes place in a non-covalent manner at the hydrophobic binding sites of HSA, however after a longer incubation time the type of the interaction is converted slowly to a protein-coordinated form [33]. Similar behavior of NAMI-A and its pyridine analogues was found recently based on mainly electron paramagnetic resonance spectroscopic measurements [34,35]. A binding ratio of four KP1019 complex anions on a single HSA molecule was determined by CD and confirmed by inductively coupled plasma atomic emission spectroscopic (ICP-AES) method [23].…”
Section: Introductionsupporting
confidence: 72%
“…The Ru-N and Ru-S bond distances of 2.109(6) and 2.2924(17) Å, respectively, are very similar to those found in the related structures containing trans-RuNCl 4 S donor set. [33][34][35]37 Three of the chlorido ligands are terminal while Cl4 forms a bridge between the ruthenium and sodium atoms. The DMSO ligand also forms a bridge between a ruthenium centre (through its sulphur atom) and a sodium (through its oxygen) thus forming a five membered RuClNaOS ring in the crystal structure.…”
mentioning
confidence: 99%
“…A pyridine-heterocycle unsubstituted analogue of 3, called NAMI-Pyr 37 and AziRu 38 ( Figure 3), has been reported to show interesting reactivity profiles towards biologically relevant targets. 9 Derivatives with functionalized pyridine ligand have also been investigated.…”
mentioning
confidence: 99%
“…Ru(III)-N-heterocyclic drugs in human trials, upon intravenous administration, can readily bind to the protein, following ligand exchange via its side chain (Hys and Cys) to form stable proteinbound adducts [52,68]. Notably, differences in NAMI-A and KP1019 protein binding may account for their distinct biological activities and cellular uptake.…”
mentioning
confidence: 99%
“…NAMI-A binding to HSA has been suggested to involve covalent interactions. However, it has also been found that the Ru(II)-reduced form of the complex favors protein binding, although the reduction is disfavored for the covalently bonded in relation to the non-covalently bonded species (which are readily reduced by ascorbic acid) [68][69][70][71]. Conversely, the binding of KP1019 to HSA occurs mostly in a noncovalent manner, probably due to favorable interactions of the indazole ligands with the hydrophobic domains of the protein [72].…”
mentioning
confidence: 99%